Una versión profesor-grupo-aula del problema de horarios - Cáceres Espinoza, Ramiro José (1998)
We present the schedule problem that include, in addition to the assignment of timing to teaching activities, the assignment of these activities to classrooms with different capacities, and that are supposed available at every time.We prove that a simple condition guaranties that activities at each time can be arranged in the classrooms, and we conclude that assignement of activities using the minimun number of time can be made in polynomial time.